2017
DOI: 10.1177/000313481708301014
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Minor hepatectomy offers a Favorable Learning Curve and May Result in Superior Perioperative Outcomes Compared with Laparoscopic Approach

Abstract: Minorhepatectomy (MH) is a common type of robotic-assisted liver resection, but few studies compared it with laparoscopic. We compared the perioperative outcomes of patients who underwent robotic (RH) or laparoscopic (LH) minor hepatectomy and evaluated the effect of surgeon's experience on outcomes. A prospective database was used to identify patients from 2009 through 2016 who underwent RH or LH. Two surgeons performed RH starting in 2014, whereas LH had been established before that. Of the 93 patients, 42 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Furthermore, another paper advised to overcome the learning curve of RLR before embarking on using robotic major liver resection for cases of malignant disease [ 26 ] in order to ensure patients’ safety, a reduced operative time, a reduced blood loss, and a high oncological quality. Two studies showed that after 25–30 robotic liver resections, the achieved perioperative outcomes might be superior to LLR [ 27 , 28 ]. However, it has to be noted that these results might depend on the surgeon’s previous experience in laparoscopic liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another paper advised to overcome the learning curve of RLR before embarking on using robotic major liver resection for cases of malignant disease [ 26 ] in order to ensure patients’ safety, a reduced operative time, a reduced blood loss, and a high oncological quality. Two studies showed that after 25–30 robotic liver resections, the achieved perioperative outcomes might be superior to LLR [ 27 , 28 ]. However, it has to be noted that these results might depend on the surgeon’s previous experience in laparoscopic liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The Da Vinci robotic surgery system can provide a better surgical field and flexible robot arms, reducing the difficulty of surgery and better avoiding damage to bile ducts and important blood vessels during the process of portal vein ligation and liver parenchymal detachment [ 15 ]. The perioperative outcomes of robotic hepatectomy are equivalent to those of laparoscopic hepatectomy and may even result in superior outcomes compared with laparoscopic hepatectomy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from randomised trials comparing laparoscopic vs open for hemi-hepatectomies (ORANGE-II PLUS) are awaited. Occun et al 48 provide a valuable review of the 14 major series (9 or more patients) of robotic liver surgery up until 2015, including all types of liver resections (major and minor) 2,39,42-44,49-57 -the big-gest, with 70 robotic liver resections, coming from Giulianotti et al 43 Since this review, a further 6 series have been published, 41,45,[58][59][60][61] totalling 627 patients of which 145 (23.1%) were for major liver resections. Some of these studies were matched with laparoscopic surgery 39,42,44,49,50,53,56,57,[59][60][61] and have shown generally comparable outcomes for blood loss, LOS, R 0 rate, operation time, morbidity and mortality.…”
Section: Major Hepatectomymentioning
confidence: 99%